2017
DOI: 10.1371/journal.pone.0172761
|View full text |Cite
|
Sign up to set email alerts
|

Classical and adaptive control of ex vivo skeletal muscle contractions using Functional Electrical Stimulation (FES)

Abstract: Functional Electrical Stimulation is a promising approach to treat patients by stimulating the peripheral nerves and their corresponding motor neurons using electrical current. This technique helps maintain muscle mass and promote blood flow in the absence of a functioning nervous system. The goal of this work is to control muscle contractions from FES via three different algorithms and assess the most appropriate controller providing effective stimulation of the muscle. An open-loop system and a closed-loop s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The results have shown that, In high-frequency stimulation, VL with more fast muscle fibers was tired faster than APB with more slow muscle fibers, and the treatment time should not exceed 14-16 min (85). Jaramillo Cienfuegos et al (86) have used a proportional integral (PI) controller to achieve classical and adaptive control of FES for isolated skeletal muscle contraction, which provided the best closed-loop performance for contraction speed and antiinterference. Future research should use algorithms to control FES muscle contraction, focusing on different stimulation sites.…”
Section: Clinical Application (Activity Function Muscle Fatigue Lates...mentioning
confidence: 99%
“…The results have shown that, In high-frequency stimulation, VL with more fast muscle fibers was tired faster than APB with more slow muscle fibers, and the treatment time should not exceed 14-16 min (85). Jaramillo Cienfuegos et al (86) have used a proportional integral (PI) controller to achieve classical and adaptive control of FES for isolated skeletal muscle contraction, which provided the best closed-loop performance for contraction speed and antiinterference. Future research should use algorithms to control FES muscle contraction, focusing on different stimulation sites.…”
Section: Clinical Application (Activity Function Muscle Fatigue Lates...mentioning
confidence: 99%